2019
DOI: 10.5572/kosae.2019.35.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Control of Fugitive Fine Coal Particulate Emissions from Coal Handling System at Coal-Fired Power Plants using a Two-Stage Vortex Scrubber

Abstract: the authors express their gratitude to tim K. takaro, md, mph, ms; Roberta Richardson, md; and molly Rauch, mph for their careful reading of the text; to Rebecca Abelman for research support and copy editing; and to jared saylor for editing. cover Art: david stuart ABouT EArThjuSTicE earthjustice is a non-profit public interest law firm dedicated to protecting the magnificent places, natural resources, and wildlife of this earth, and to defending the right of all people to a healthy environment. We bring about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The other type of wet scrubber unit is the vortex scrubber (Brauer and Varma, 2012). CFD calculations carried out on double vortex scrubber concluded that the performance is better with a double vortex system than a single vortex system (Kim et al 2019). In order to impede the flow of dust and smoke, a filtration device like the electrostatic precipitator (ESP) are also studied (Gromaszek et al 2016).…”
Section: Pollutant Dispersion: Particulate Matter (Pm)mentioning
confidence: 99%
“…The other type of wet scrubber unit is the vortex scrubber (Brauer and Varma, 2012). CFD calculations carried out on double vortex scrubber concluded that the performance is better with a double vortex system than a single vortex system (Kim et al 2019). In order to impede the flow of dust and smoke, a filtration device like the electrostatic precipitator (ESP) are also studied (Gromaszek et al 2016).…”
Section: Pollutant Dispersion: Particulate Matter (Pm)mentioning
confidence: 99%